Budd Chiari syndrome in a patient with Celiac disease: A rare entity - Ismail, Hina; Majid, Zain; Shah, Zahid; Abrar, Ghazi; Taha Yaseen Khan, Raja; Hanif, Farina; Hassan Luck, Nasir (Asian Journal of Medical Sciences, 2021)
Celiac disease is an immune mediated enteropathy that causes malabsorption. It is associated with a number of autoimmune diseases, however is rarely associated with Budd chiari syndrome. We present a case of a young girl who was a diagnosed case of celiac disease and had presented with abdominal distension along with pedal edema. Her initial workup was all negative while ultrasound abdomen along with CT scan abdomen had given the impression of Budd chiari syndrome. She was managed with gluten free diet, diuretics along with anticoagulants.